Endodontic management of mandibular second premolar with three roots and three root canals: A case report - Nidhi Shrivastava; Marisha Bhandari (Wolters Kluwer Medknow Publications, 2014)
High level of success in endodontic treatment requires an understanding of root canal anatomy and morphology. The clinician must be prepared to identify those teeth that tend to vary generally from norm. Thorough debridement and obturation of such teeth can be challenging and failing to do so can lead to treatment failure. Mandibular premolars have earned the reputation for having aberrant anatomy. However, the occurrence of three separate canals with three separate foramina in mandibular premolars is very rare. The incidence of three canals is as high as 23% in mandibular first premolars, whereas in second premolars incidence is as low as 0.4%. Three rooted mandibular second premolar is reported to be 0.2%. This case report describes endodontic management of one such tooth with unusual morphological variations in canal anatomy of mandibular second premolar.